Connections Unveiled: A Bibliometric Study of Relationship Marketing - Kania Widyatami; Ratih Hurriyati; Puspo Dirgantari; Sri Astuti Pratminingsih (International Journal of Economics Development Research (IJEDR), 2023)
Over the past four decades, relationship marketing has captured the interest of scholars, resulting in a vast amount of literature. Thus, the field merits a review article that can help scholars navigate the cumulated research. This study employs bibliometric analysis of the Scopus database from 1987–2022. The data was then analysed using Microsoft Excel, R software’s “bibliometrix” package, and the Publish or Perish applications. The results reveal key trends as well as the intellectual, knowledge, and conceptual structure in the field that give scholars a comprehensive outline of the relationship marketing field as well as insights about future research.